Adolescent resilience following childhood maltreatment - Smith, Caroline (The University of Edinburgh, 2014)
Background: Previous research has demonstrated that a history of childhood maltreatment can lead to significant negative consequences across multiple domains of functioning. A significant minority of individuals remain resilience to such negative consequences, necessitating further research into the factors which protect against negative outcomes in young people who have experienced adversity. A systematic review of the literature was carried out in order to assess the evidence base for factors that predict adolescent resilience following childhood maltreatment. Several factors across the individual, family and community level were identified, however, evidence regarding these factors was mixed. Factors that have been shown to predict resilience in other age groups require further validation within adolescent samples. Aim: The first aim of this study was to investigate the role of resilience in the relationship between childhood maltreatment and psychological distress. The second aim was to address a possible role for attachment in mediating the relationship between childhood maltreatment and resilience. Method: Adolescents aged 13 – 17 who were attending Child and Adolescent Mental Health Services were asked to complete measures of childhood maltreatment, individual resilience, attachment and psychological distress. Results: Resilience was shown to mediate the relationship between maltreatment and psychological distress. Attachment avoidance was found to mediate the relationship between maltreatment and resilience but not when emotional reactivity was included in the resilience index. Attachment anxiety did not mediate the relationship between maltreatment and resilience, however, maltreatment history was found to moderate the relationship between attachment anxiety and resilience. Discussion: Generalisability of this study was limited due to possible bias within the recruited sample. Implications of the significant results are discussed along with suggestions for future research.
Keywords: child abuse; adolescent; resilience; attachment; psychological distress